Transformation of traditional games as an innovative method to enhance student learning motivation - Nurlaila, Nurlaila; Siantoro, Gigih; Hidayat, Taufiq; Nur Shodiq, Moh. (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2025)
This quantitative study investigates the effectiveness of transforming traditional games into innovative instructional media to enhance elementary school students’ learning motivation in Physical Education, Sports, and Health (PJOK). Utilizing a one-group pretest–posttest design, the research was conducted with 40 fifth-grade students at SD Nurul Ulum, Surabaya, during the 2024/2025 academic year. The intervention comprised five PJOK sessions integrating modified versions of gobak sodor, boy-boyan, benteng-bentengan, and lari balok. Motivation was measured using a 29-item questionnaire, which demonstrated excellent reliability (? = 0.90). Data analysis via SPSS included tests for normality (Kolmogorov–Smirnov, Shapiro–Wilk) and a one-sample t-test for pre- and post-intervention scores. Results revealed a significant increase in motivation, with mean scores rising from 70.18 (SD = 3.67) to 89.33 (SD = 2.96), p < 0.05. This implies that the enjoyable, collaborative, and culturally contextual nature of transformed traditional games effectively fosters intrinsic motivation and supports culturally relevant pedagogy. The study concludes that integrating traditional games into PJOK is a viable innovative method to boost student motivation, preserve local cultural values, and enrich learning experiences.This result strengthens the urgency of integrating local culture in elementary school learning, as well as being a concrete step in supporting the Merdeka Learning policy that emphasizes the meaningfulness, diversity, and relevance of learning.